Current perspectives on the interleukin-1 family as targets for inflammatory disease. - Walsh, Patrick; Lucitt, Margaret (My University, 2019)
Since the ﬁrst description of interleukin-1 (IL-1) and the genesis of the ﬁeld of cytokine biology, the understanding of how IL-1 and related cytokines play central orchestrat- ing roles in the inﬂammatory response has been an area of intense investigation. As a consequence of these endeavours, speciﬁc strategies have been developed to target the function of the IL-1 family in human disease realizing signiﬁcant impacts for patients. While the most signiﬁcant advances to date have been associated with inhibition of the prototypical family members IL-1α/β, approaches to target more recently identiﬁed family members such as IL-18, IL-33 and the IL-36 subfamily are now beginning to come to fruition. This review summarizes current knowledge surrounding the roles of the IL- 1 family in human disease and describes the rationale and strategies which have been developed to target these cytokines to inhibit the pathogenesis of a wide range of diseases in which inﬂammation plays a centrally important role.
PUBLISHED
Keywords: Canakinumab; Inflammation; Inflammatory disease; Interleukin-1 family; Therapy